The Portrayal of Queen Semiramis as a Warrior – Queen in Selected English Children’s Literature - Zahraa Muthana, Researcher; Ansam Yaroub Khyoon, Prof. (lark, 2023)
Queen Semiramis is considered the most famous Mesopotamian queen compared to other queens from different civilizations. Greek historians were the first to record her history by adding some mythical elements to her story making it a great legend that survived till this day. Due to the queens’ great character, her legend is retold to children by many children writers. In this research, two children adaptations; Semiramis: Child Of The Doves by Marianna Mayer (1999) and Queen Semiramis: The Legend (2020) by Ingrid de Haas were taken as examples of the portrayal of queen Semiramis personality as a warrior queen during the Assyrian civilization. The researchers compared and contrasted the children adapted versions to Semiramis Legend by Diodorus Siculus, the original legend of the queen. The researchers concluded that, although many details were either changed or deleted compared to the original legend, yet all changes did not affect her portrayal as a warrior – queen with great achievements.
Keywords: Assyrian Civilization, Mesopotamia, warrior – queen